Human CLC-K Channels Require Palmitoylation of Their Accessory Subunit Barttin to Be Functional - Steinke, Kim Vanessa (J Biol Chem, 2015)
CLC-K/barttin chloride channels are essential for NaCl re-absorption in Henle's loop and for potassium secretion by the stria vascularis in the inner ear. Here, we studied the posttranslational modification of such channels by palmitoylation of their accessory subunit barttin. We found that barttin is palmitoylated in vivo and in vitro and identified two conserved cysteine residues at positions 54 and 56 as palmitoylation sites. Point mutations at these two residues reduce the macroscopic current amplitudes in cells expressing CLC-K/barttin channels proportionally to the relative reduction in palmitoylated barttin. CLC-K/barttin expression, plasma membrane insertion, and single channel properties remain unaffected, indicating that these mutations decrease the number of active channels. R8W and G47R, two naturally occurring barttin mutations identified in patients with Bartter syndrome type IV, reduce barttin palmitoylation and CLC-K/barttin channel activity. Palmitoylation of the accessory subunit barttin might thus play a role in chloride channel dysfunction in certain variants of Bartter syndrome. We did not observe pronounced alteration of barttin palmitoylation upon increased salt and water intake or water deprivation, indicating that this posttranslational modification does not contribute to long term adaptation to variable water intake. Our results identify barttin palmitoylation as a novel posttranslational modification of CLC-K/barttin chloride channels.